Impact of a free public transportation service for rural households - Slamet Rosyadi; Shadu S. Wijaya; M. Husnul Maab; Zaula Rizqi Atika; Chamid Sutikno (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The transportation service subsidy is intended to ease the burden of students from low-income families by helping with their need for mobility. The local government provides a transportation service expenditure budget annually to pay for the transportation services they require. Theoretically, the subsidy benefits the poor, although a study on the evaluation of the transportation service subsidy program is still needed to ascertain whether the program beneficiaries benefit from the program. This study used a survey method, and it deepened by the in-depth interviews conducted with 98 respondents. It used to obtain supporting information to pair with the survey results. The critical findings from this study are that the subsidy program has increased the rate of savings in terms of transportation service spending, and it has also reduced the burden of food expenditure among the poor. Better access to education services among the program recipient students reduced traffic congestion, and the enthusiasm for learning within low-income family students are also benefits. Another benefit is that the public transport drivers involved in the program get sustainable income certainty. The income of the recipient community groups has increased moderately compared to the non-recipient groups. However, saving on transportation spending does not contribute significantly to the burden of food expenditure for low-income families. The reason for this is that the free transportation subsidies received by the poor are minimal in terms of the frequency of coupon use. This study concludes that free transport subsidies in the short term can alleviate the burden on the poor, and in the long run, they can improve the welfare of the poor.